Publiczne finansowanie sztuki w kontekście zasady neutralności światopoglądowej państwa – podejście filozoficznoprawne - Wojdala, Magdalena (Filozofia Publiczna i Edukacja Demokratyczna, 2016)
The aim of the article is to analyze the issue of public funding of art in the context of state’s neutrality principle. In the first part of the paper I present theoretical dimension of the problem of neutral and perfectionist justification for public authorities’ actions. The second part of the article comprises the outline and the critique of a few arguments which justify funding of art from public treasury. I concentrate particularly on Ronald Dworkin’s conception. In summary I present three possible model solutions of the problem of public funding of art.